Immunological and clinical parameters of newcastle disease vaccination in bronze Turkeys (Meleagris gallopavo) - Schmidt, Elizabeth Moreira dos Santos [UNESP]; Paulillo, Antonio Carlos [UNESP]; Martins, Gislaine Regina Vieira [UNESP]; Denadai, Janine [UNESP]; Lapera, Ivan Moura [UNESP] (My University, 2010)
Clinical and immunological aspects of female Bronze Turkeys, on breeding season, vaccinated against Newcastle disease were evaluated. Seventy-five female Turkeys were distributed into five different experimental groups, vaccinated or not against Newcastle disease: G1 (Ulster 2C strain), G2 (B1 strain), G3 (LaSota strain), G4 (LaSota strain inactivated and emulsified in mineral oil) and G5 (not vaccinated-control). The immune response was evaluated by the HI test. Female Turkeys showed high antibody titres when vaccinated against Newcastle disease with live LaSota and inactivated LaSota strains and a moderated to elevated antibody response when vaccinated with Ulster 2C and B1 strains. No clinical signs associated with post-vaccinal reactions were observed. © Asian Network for Scientific Information, 2010.
Keywords: B1 and LaSota strains; Bronze Turkeys; Meleagris gallopavo; Newcastle disease; Ulster 2C; Vaccination